Determination of the antioxidant properties of ethanol and water extracts from different parts of Teucrium parviflorum Schreber - Turkoglu, Semra; Celik, Sait; Turkoglu, Ismail; Cakilcioglu, Ugur; Bahsi, Muammer (Academic Journals, 2010)
This study was designed to examine in vitro antioxidant of extracts of Teucrium parviflorum Schreber. The plants were extracted successively in ethanol and water using soxhlet-apparatus. They were screened for possible antioxidant activity using the ABTS(center dot) (2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid)) radical scavenging capacity, DPPH center dot (2,2-diphenyl-1-picrylhydrazyl) radical scavenging capacity, superoxide anion radical scavenging capacity, hydrogen peroxide scavenging capacity, reducing power and metal chelating activities. These various antioxidant activities were compared with standard antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and alpha-tocopherol. The extracts of T. parviflorum showed strong antioxidant activity and effective antioxidant assay. This antioxidant property depends on concentration and increase with increased amount of sample. In addition, total phenolic compounds in the extracts of T. parviflorum were determined as pyrocatecol equivalents. The results obtained in the present study indicated that T. parviflorum is a potential source of natural antioxidant.
Keywords: Teucrium parviflorum; antioxidant activity; medicinal plants; extract; flower; leaves